2019
DOI: 10.1186/s13104-019-4178-3
|View full text |Cite
|
Sign up to set email alerts
|

No detection of EBV, BKV and JCV in breast cancer tissue samples in Iran

Abstract: ObjectiveThe most common cancer amongst women is breast cancer. Reports on the role of EBV, BKV, and JCV in the development of breast cancer are controversial. Hence, the aim of this study was to determine the frequency of EBV, BKV, and JCV in malignant breast tumors in comparison with benign ones.ResultsA total of 300 breast biopsy tissues were included, of which 150 were malignant and 150 benign. After deparaffinization, tissues were subjected to DNA extraction. β-globin gene was amplified by PCR to evaluate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 34 publications
0
15
0
Order By: Relevance
“…54 However, EBV DNA was not detected in FFPE tissues of Iranian women using PCR targeting the Bam HI-H rightward open reading frame 1 (BHRF1) region. 55 Moreover, EBV DNA was detected using PCR in 20% of fresh tissues of Egyptian BC patients, 56 4.7% of Mexican BC patients, 57 and 31% of Argentinian BC patients. 58 These lower detection rates could be due to differences in storage methods of samples.…”
Section: Discussionmentioning
confidence: 99%
“…54 However, EBV DNA was not detected in FFPE tissues of Iranian women using PCR targeting the Bam HI-H rightward open reading frame 1 (BHRF1) region. 55 Moreover, EBV DNA was detected using PCR in 20% of fresh tissues of Egyptian BC patients, 56 4.7% of Mexican BC patients, 57 and 31% of Argentinian BC patients. 58 These lower detection rates could be due to differences in storage methods of samples.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, Littman et al reported that EBV antibody titers and old-age at primary infection with EBV might have a role in the etiology of ovarian cancer ( 38 ). Although it is early to conclude the role of EBV in the development of ovarian cancer, the role of this virus in some important human cancers such as, Burkitt lymphoma, nasopharyngeal carcinoma and gastric cancer is well-defined ( 39 ).…”
Section: Discussionmentioning
confidence: 99%
“…Biopsies of the uterine cervix showed that the EBV receptors are mostly expressed on ecto-and endo-cervix regions, therefore, it might be involved in the development of cervical cancer as a "helper" factor (Thoe et al, 1993;Shi et al, 2016). Regarding new reports, the presence of EBV has been documented in other cancers including breast, prostate, oral, and salivary gland carcinomas (Sarvari et al, 2018;Dowran et al, 2019).…”
Section: Introductionmentioning
confidence: 99%